Readability of Sundanese Textbooks for Grade VIII Junior High School Students: An Analysis Based on the Fry Readability Graph - Zahra, Fanatria; Kuswari, Usep; Awaliah, Yatun Romdonah; Nugraha, Haris Santosa (Jurnal Paedagogy, 2026)
This study aims to analyze and compare the readability levels of Sundanese language textbooks for eighth-grade junior high school students using Fry’s Readability Graph. The research employed a descriptive method with a qualitative approach. Data were collected through document analysis by examining the discourses contained in the textbooks. The objects of this study were the Rancagé Diajar Basa Sunda Grade VIII textbook published by Pustaka Jaya and the Wiwaha Basa Grade VIII textbook published by Geger Sunten. Data analysis was conducted using the Fry Graph formula by calculating the average number of sentences and syllables per 100 words, which were then plotted on the Fry Graph to estimate the readability levels of the texts. The results indicate that the Rancagé Diajar Basa Sunda textbook falls within the readability range of grades 5–7, whereas the Wiwaha Basa textbook falls within the range of grades 6–8, making it more appropriate for the expected reading ability of eighth-grade students. These findings provide valuable insights for teachers and textbook authors to pay greater attention to linguistic features and text structure in the development of instructional materials. Consequently, this study contributes to improving the quality of Sundanese language textbooks and supports more effective learning that is aligned with students’ reading abilities.